2019
DOI: 10.1101/563759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput targeted gene deletion in the model mushroom Schizophyllum commune using pre-assembled Cas9 ribonucleoproteins

Abstract: Efficient gene deletion methods are essential for the high-throughput study of gene function. Compared to most ascomycete model systems, gene deletion is more laborious in mushroom-forming basidiomycetes due to the relatively low incidence of homologous recombination (HR) and relatively high incidence of non-homologous end-joining (NHEJ). Here, we describe the use of pre-assembled Cas9-sgRNA ribonucleoproteins (RNPs) to efficiently delete the homeodomain transcription factor gene hom2 in the mushroom-forming b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been successfully applied to genome editing in animals, plants and microbes (Arazoe et al, 2015;Bortesi et al, 2016;Li et al, 2019;Schultz et al, 2019). Recently, the CRISPR/Cas9 system has been used for the disruption of genes in higher fungi such as Coprinopsis cinerea, Cordyceps militaris and Schizophyllum commune (Sugano et al, 2017;Chen et al, 2018;Vonk et al, 2019). Qin et al reported the disruption of the ura3 gene of G. lucidum and G. lingzhi, which revealed the potential of the CRISPR/Cas9 system for disrupting the genes of Ganoderma (Qin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been successfully applied to genome editing in animals, plants and microbes (Arazoe et al, 2015;Bortesi et al, 2016;Li et al, 2019;Schultz et al, 2019). Recently, the CRISPR/Cas9 system has been used for the disruption of genes in higher fungi such as Coprinopsis cinerea, Cordyceps militaris and Schizophyllum commune (Sugano et al, 2017;Chen et al, 2018;Vonk et al, 2019). Qin et al reported the disruption of the ura3 gene of G. lucidum and G. lingzhi, which revealed the potential of the CRISPR/Cas9 system for disrupting the genes of Ganoderma (Qin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on these two model species using tools such as DNA-mediated transformation, RNA interference, and CRISPR/Cas9 etc. have pioneered our knowledge of the multicellular development, mating pheromone, and receptor signaling pathways in the Agaricomycetes [14][15][16][17][18]. More recently, studies also focused on ecologically or economically important non-model species, which included the saprotrophic fungi (Agaricus bisporus, Flammulina filiformis, Lentinula edodes, Lentinus tigrinus, Cyclocybe aegerita), plant pathogen (Armillaria ostoyae), and the ectomycorrhizal fungi (Laccaria bicolor) [2,[19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The sgRNAs were designed on regions downstream and upstream of the up-flank and downflank of roc1, respectively, and one sgRNA was selected for each region as previously described 17 .…”
Section: Deletion Of Gene Roc1 In Strain H4-8mentioning
confidence: 99%
“…In general, very little is known about the regulatory mechanisms involved in plant biomass degradation in the basidiomycetes.Schizophyllum commune is a model system for mushroom-forming fungi in the class Agaricomycetes. Several molecular tools have been developed for this organism, including an efficient gene deletion protocol 17,18 and a ChIP-Seq protocol for Histone H3 to study the epigenetic landscape 19 .S. commune has a wide geographical distribution and is generally found as white fruiting bodies growing on wood.…”
mentioning
confidence: 99%
See 1 more Smart Citation